Effect of Family Environment and Education Costs on StudentAchievement with Interest in Reading as an Intervening Variable - Sutriayu, Sutriayu; Makhdalena, Makhdalena; Sumarno, Sumarno (FKIP-Universitas Riau, 2020)
Learning entrepreneurship is very important for special students in vocational high schools (SMK). However, there are still many students getting entrepreneurial grades under the standard (KKM). It can be said that student achievement in entrepreneurship subjects is low, this is inseparable from the factors that influence learning achievement such as: family environment, education costs, and reading interest. The research objective is to look at the effect of family environment and educational costs on student achievement both simultaneously and partially and to see the influence of family environment, education costs, and reading interest on learning achievement both simultaneously and partially. The population in this study was the entire class XI Pharmacy Pharmacy Ikasari Pekanbaru with 249 students. The sampling technique used Simple Random Sampling with a sample size of 153 students. The data in this study were secondary data obtained from school documents in the form of student daily test scores and primary data obtained from questionnaires filled out by students. The results showed that family environment and education costs had a positive and significant effect on learning achievement both 43.4% simultaneously and partially with a large coefficient of peht 43.6% and 39.7% and family environment, education costs,and reading interest positive and significant effect both simultaneously at 56.3% and partial with a peht coefficient of 16.5%, 13.2%, and 57.3%.